2018
DOI: 10.12968/jowc.2018.27.5.310
|View full text |Cite
|
Sign up to set email alerts
|

Perception of diabetic foot ulcers among general practitioners in four European countries: knowledge, skills and urgency

Abstract: The intra-country and inter-country management of the complex aspects of DFU is quite heterogeneous. The cause of this finding is multifactorial. Although there are international guidelines, it would be beneficial to establish clear and specific competencies for the different health professionals involved in DFU management. As a minimum, intra-country heterogeneity should improve with their development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…However, the adoption and implementation of the recommendations in clinical practice is rather disappointing and a National Health Survey in 2010 in the United Kingdom reported that more than 50% of individuals with diabetes do not recollect having their feet examined or being given any advice regarding foot care (42). One recent study examined perception and knowledge of the pathogenesis and management of DFU among 600 general practitioners (GPs) in four countries in Europe-France, United Kingdom, Spain, and Germany (150 GPs per country) (45). A total of 1,188 patient cases from the four countries were also collected.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adoption and implementation of the recommendations in clinical practice is rather disappointing and a National Health Survey in 2010 in the United Kingdom reported that more than 50% of individuals with diabetes do not recollect having their feet examined or being given any advice regarding foot care (42). One recent study examined perception and knowledge of the pathogenesis and management of DFU among 600 general practitioners (GPs) in four countries in Europe-France, United Kingdom, Spain, and Germany (150 GPs per country) (45). A total of 1,188 patient cases from the four countries were also collected.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are international guidelines, it would be beneficial to establish clear and specific competencies for the different health professionals involved in diabetic management. As a minimum, intra-country heterogeneity should be reduced with their development (Garciaklepzig et al, 2018;Ogilvie, Patel, Venkat Narayan, & Mehta, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sayah, Soprovich, Qiu, Edwards, and Johnson (2015) found only 14% T2DM patients (N = 2040) performed foot self-care 6 days per week or more often. Almost 30% of general practitioners (GPs) in France and Germany thought diabetic foot ulcer (DFU) treatment was not well established due to the absence of clinical guidelines and protocols (Garciaklepzig et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…According to recent literature, PVD, which is associated with lower probability of healing, longer healing times, higher probability of recurrence and greater risk of amputation, is now estimated to be present in a majority of patients with a DFU. 7,[43][44][45][46] Early detection of DFUs and prompt referral by both the patient and health professional has been demonstrated to be crucial for optimal healing, reduction of amputation risk and of treatment cost. 5,25,47 First assessment by foot specialist comprehends in a holistic approach the identification of medical history and comorbidities of the patient, aetiology of the wound, biological and clinical exams, including an assessment of the foot perfusion which may lead to revascularisation if required, the investigation of local signs of infection, and the initiation of infection treatment if required, to avoid rapid deterioration of the DFU.…”
Section: Discussionmentioning
confidence: 99%
“…48 Reinforcing and supporting the education of health professionals and patients to these and to the need for surveillance of DFUs and their complications is essential. 2,[46][47][48] While new effective treatments and evidence-based treatment decisions can help to increase closure rate and gain time-to-closure in the management of these chronic wounds, additional efforts should be made to increase the early detection of DFUs and the prevention of their recurrence, notably by highlighting the importance of foot surveillance and hyperkeratosis removal. 2 Patients with diabetes may find it difficult to detect a new wound due to neuropathy and if a possible plantar wound location.…”
Section: Discussionmentioning
confidence: 99%